( cos ( 8 0 ∘ ) × cos ( 2 0 ∘ ) × cos ( 6 0 ∘ ) × cos ( 4 0 ∘ ) ) − 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
One might argue that applying the triple angle trigonometric formula 4 cos ( A ) cos ( 6 0 ∘ − A ) cos ( 6 0 ∘ + A ) = cos ( 3 A ) is simpler.
cosA.cos2A.cos4A.cos8A............... upto n terms
=sin(2 Greatest angle)/2^(Total number of terms) sin(Smallest angle)
In this case,
(sin2x80)/(2^4)(sin20)
=(sin160)/16sin20
=sin20/16sin20
=1/16
Answer = (1/16)^-1 = 16
Best approach. Well done
Been a while since I used Chebyshev polynomials, so here we go.
We're working with CP of the first kind. Ignore the 60 for now so we have cos ( 2 0 ) cos ( 4 0 ) cos ( 8 0 ) . Our polynomial will be of degree three and have roots of cos ( 3 θ ) . The first coefficient is 2 to the power of the degree of the equation-1.
2 2 x 3 + . . . + 0 = cos ( 3 ⋅ 2 0 )
4 x 3 + . . . − 1 / 2 = 0
The product of this polynomial's roots is the negation of the last coefficient divided by the first.
− 4 − 1 / 2 = 8 1 . Multiplying this by cos ( 6 0 ) we have our answer 1 6 1
There you go. Very easy approach. Well done! :)
Problem Loading...
Note Loading...
Set Loading...
We know that cos 6 0 ° = 2 1 and the value of the rest of the expression becomes 2 1 ( 2 3 sin 2 0 ° 1 ) . sin ( 2 3 . sin 2 0 ° ) ⇒ 1 6 1 × sin 2 0 ° 1 . sin 1 6 0 ° ⇒ 1 6 sin 2 0 ° 1 . sin ( 1 8 0 ° − 2 0 ° ) ⇒ 1 6 1 ( sin 2 0 ° sin 2 0 ° ) = 1 6 1 Hence the inverse of the given expression is ( 1 6 1 ) − 1 = 1 6